Penerapan Sistem Pakar untuk Mengukur Tingkat Stres Kerja Karyawan dengan Menggunakan Metode Forward Chaining - Achmad Muzakir; Agus Budiyantara (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
An expert system is a computer-based program designed to simulate the reasoning and decision-making abilities of an expert in a particular field, enabling it to serve as a reference for specific conditions. This system integrates knowledge, rules, and experiences obtained from experts to support problem identification, provide recommendations, and determine appropriate decisions accurately. In this study, the expert system is utilized to measure employee stress levels based on the symptoms experienced by users. The diagnostic process is carried out using the forward chaining method, a reasoning technique that begins with facts or symptoms provided by the user and then matches them with IF–THEN rules to generate a conclusion or diagnostic result. Through the implementation of this method, the system is capable of providing employee stress assessments in a more structured, systematic, and rule-based manner according to the predefined knowledge base. The final outcome of this research is the development of a forward chaining–based expert system for measuring employee stress within a company environment, which can assist the diagnostic process more effectively and accurately.